Penerapan Workplace Stretching Exercise untuk Mengurangi Keluhan Nyeri Otor Rangka Pekerja Pembibitan Jamur - Tri Wahyuni; Yamtana Yamtana; Sri Muryani (Poltekkes Kemenkes Yogyakarta, 2020)
One of the occupations that have great risk of musculoskeletal disorders (MSDs) is mushroom seeding workers. The results of a preliminary study in mushroom home industries showed that 100% workers complaining of pain in the limbs after work so that efforts to overcome this situation is needed. The purpose os the study was to reduce the complaints of musculoskeletal disorders among mushroom seeding workers in Klangon Village of Argosari, Sedayu, Bantul by implementing workplace stretching exercise. The study was a quasi-experiment with pre-test posttest with control group design. The exercise interventions were given in five days with one frequency a day, and 8-10 minute duration per session. The study samples were 31 female workers who were selected by using simple random sampling technique. The instrument used was the Nordic Body Map questionnaire with 17 sekeletal muscle focus points. The data were analysed by using Wilcoxon Rank Test and Mann Whitney at ?=0,05. The results showed that the reduction average of musculoskeletal disorders in the experiment group was 84,16%, meanwhile in the control group it was 7,16%. The p-value obtained from statistical analysis was <0,001 indicating that the reduction different between the two study groups was significant. To conclude, workplace stretching exercise can reduce musculoskeletal disorders among mushroom seeding workers.